2015
DOI: 10.1089/fpd.2015.1959
|View full text |Cite
|
Sign up to set email alerts
|

EnterotoxigenicEscherichia coliSubclinical Infection in Pigs: Bacteriological and Genotypic Characterization and Antimicrobial Resistance Profiles

Abstract: Enterotoxigenic Escherichia coli (ETEC) is the major pathogen responsible for neonatal diarrhea, postweaning diarrhea, and edema disease in pigs. Although it can be harmless, ETEC is also present in the intestines of other animal species and humans, causing occasional diarrhea outbreaks. The evaluation of this pathogen's presence in food sources is becoming an increasingly important issue in human health. In order to determine the prevalence of ETEC in nondiarrheic pigs, 990 animals from 11 pig farms were samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
5
26
1
2
Order By: Relevance
“…Our present study showed varied genetic diversity between three strains of neonatal meningitis E. coli (NMEC) isolated from WWTP nal e uent and river water samples and this is in line with a study by Levert et al [72] who reported genetic diversity of extraintestinal pathogenic strains of E. coli. In this study, STEC had the highest number of ERIC-PCR genotypes and our ndings are in contrary with the report by Moredo et al [73] where ETEC reportedly had the highest EPIC-PCR genotypes. Studies by Yasir et al [74] and Sun et al [75] reported the genetic diversities in multidrug resistant ESBLproducing E. coli although, our study did not screen for ESBL in the E. coli strains nevertheless provides an opportunity for further analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Our present study showed varied genetic diversity between three strains of neonatal meningitis E. coli (NMEC) isolated from WWTP nal e uent and river water samples and this is in line with a study by Levert et al [72] who reported genetic diversity of extraintestinal pathogenic strains of E. coli. In this study, STEC had the highest number of ERIC-PCR genotypes and our ndings are in contrary with the report by Moredo et al [73] where ETEC reportedly had the highest EPIC-PCR genotypes. Studies by Yasir et al [74] and Sun et al [75] reported the genetic diversities in multidrug resistant ESBLproducing E. coli although, our study did not screen for ESBL in the E. coli strains nevertheless provides an opportunity for further analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…No cross protection between F18ab and F18ac was observed on vaccination against F18 variants [53]. A nonfimbrial adhesin identified as AIDA (adhesin involved in diffuse adherence) has been observed to be associated with ETEC strains recovered from pigs with PWD [54]. In this study, 50.0% of isolates were ETEC-aidA + .…”
Section: Determining Factorsmentioning
confidence: 60%
“…For example and as mentioned earlier, the autotransporter protein AIDA is a non-fimbrial adhesin that is expressed by certain strains causing PWD in pigs (31, 496, 497). Iha is another adhesin usually associated with shigatoxin-producing E. coli that can be detected in some animal ETEC (495, 498).…”
Section: Other Virulence Factorsmentioning
confidence: 88%